2011
DOI: 10.2139/ssrn.1833344
|View full text |Cite
|
Sign up to set email alerts
|

Do Markets Perceive Sukuk and Conventional Bonds as Different Financing Instruments?

Abstract: Do markets perceive sukuk and conventional bonds as different financing instruments? AbstractThe last decade witnessed a proliferation in issues of sukuk, Islamic financial instruments structured to replicate the cash flows of conventional bonds. Using a market-based approach on Malaysian data, we consider whether investors react differently to the announcements of sukuk and conventional bond issues. Our findings suggest the stock market is neutral to announcements of conventional bond issues, but reacts negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 25 publications
0
30
1
Order By: Relevance
“…Over the first decade of the 21st century the market witnessed several Sukuk issuances in different forms and structures. Since 2001, a greater number of entities such as government and corporations have started issuing Sukuk and hence establishing the Sukuk market (Saeed and Salah, 2014 Godlewski, 2011).…”
Section: Development Of the Sukuk Industrymentioning
confidence: 99%
“…Over the first decade of the 21st century the market witnessed several Sukuk issuances in different forms and structures. Since 2001, a greater number of entities such as government and corporations have started issuing Sukuk and hence establishing the Sukuk market (Saeed and Salah, 2014 Godlewski, 2011).…”
Section: Development Of the Sukuk Industrymentioning
confidence: 99%
“…Thus, the market associates higher risks to sukuk structures rather than conventional structures. Godlewski, Turk-Ariss, & Weill (2011) suggested that an adverse selection can cause this phenomenon. Firms with lower profit expectations tend to issue profit-loss-sharing based sukuk, while firms with higher profit expectations issue interest-based conventional bonds."…”
Section: Resultsmentioning
confidence: 99%
“…Another group of authors (Godlewski, Turk-Ariss, & Weill, 2011 has addressed the same question -are sukūk and bonds different -from a different angle. They try to identify differences indirectly by observing the reaction of some variables such as stock prices on comparable "events" in the bond or sukūk markets.…”
Section: Sukūk Issuance As Risk Signal In the Stock Marketsmentioning
confidence: 99%
“…The study's results confirm that market risk, credit risk, operational risk and liquidity risk significantly influence the sukuk returns. Godlewski, Turk, and Weill (2011) using Malaysian sukuk data, empirically examine whether investors react differently to the announcements of sukuk and conventional bond issues. They conclude that "the stock market is neutral to announcements of conventional bond issues, but reacts negatively to the announcements of sukuk issues."…”
Section: Theoretical Issues and Literature Reviewmentioning
confidence: 99%